The Perspective Plan for Tamil Nadu 1974-84 - Planning Commission (Planning Commission, 1974)
Compatibility with the National Objectives— The Constitution has made both the Union Government and the State Governments responsible for social and economic planning by placing the subject in the concurrent list. Success of planning requires that planning at the National and State levels is towards similar goals. The objectives of the Perspective Plan of Tamil Nadu are compatible with the main objectives of Self Reliance and Removal of Poverty adopted by the National Fifth Plan. Doubling the per capita real income The population of Tamil Nadu in 1971 was 241 millions. The per capita income at 1970-71 prices (old series) was Rs. 654. The objective therefore is to achieve a Per Capita income of Rs 1,308 in 1983-84 (at 1970-71 prices) for a population estimated to be 53.69 millions in 1984. This is an ambitious task. While the going will be tough the objective is attainable. To achieve this, a strategy which combines production and distribution functions with employment as the central aim has been adopted.
State Planning Commission Ezhilagam Madras
Government of Tamil Nadu